How to preach and teach the Old Testament for all its worth : a follow-up to how to read the Bible for all its worth - Wright, Christopher J. H. 1947- (Zondervan, 2016)
Many preachers ignore preaching from the Old Testament because they feel it is outdated in light of the New Testament and difficult to expound. On the other hand, some preachers will preach from the Old Testament frequently but fail to handle it correctly, turning it into moralistic rules or symbolic lessons for our spiritual life. In How to Preach and Teach the Old Testament for All Its Worth, Christopher J.H. Wright proclaims that preachers must not ignore the Old Testament. It is the Word of God! The Old Testament lays the foundation for our faith and it was the Bible that Jesus read and used. Looking first at why we should preach from the Old Testament, the author moves on to show the reader how they can be preach from it. Covering the History, Law, Prophets, Psalms, and Wisdom Literature, interspersed with practical checklists, exercises, and sermons, he provides an essential guide on how to handle the Old Testament responsibly. -- Amazon.com.